Reledmac. Typesetting technology-independent critical editions with LaTeX - Dunning, A (Institut für Dokumentologie und Editorik, 2020)
Reledmac, an open-source package for the LaTeX typesetting system, offers a reliable method to arrange text on a page with multiple levels of scholarly apparatus and commentary. Its straightforward interface and wide availability has allowed its use in several projects aiming to visualize an edition encoded in TEI XML in a printed format.